An NGS‐based approach to identify Y‐chromosome variation in non‐obstructive azoospermia. (4th August 2021) - Liu, Yongjie; Wang, Guoping; Zhang, Fan; Dai, Liang
Abstract: Copy number variations (CNVs), including deletions and duplications on the Y chromosome, are known genetic factors in azoospermia. Therefore, it is important to identify novel pathogenic CNVs related to azoospermia. In this study, we compared CNVs detected by STS‐PCR and NGS in 107 individuals with nonobstructive azoospermia (NOA). STS‐PCR analysis revealed that 8.14% (9/107) of patients had AZF deletions. The highest percentage of deletions was located in the AZFc region, followed by AZFa and AZFb+c. Positive CNVs, including four duplications, six deletions and three complex CNVs, were detected using NGS methods in 12.15% (13/107) of NOA patients. Both the duplications and deletions detected in q11.223 were confirmed to increase the genetic risk for NOA. A comparison between the STS‐PCR results and NGS methods revealed concordant CNV‐positive results in 4 of 107 cases (3.74%). The discrepancies included 6 cases with CNVs identified by NGS but not detected by STS‐PCR, and two cases were detected by STS‐PCR but not by NGS. Notably, four duplications were not identified and three complex CNVs were detected as simple deletions using STS‐PCR analysis. The NGS method provides comprehensive results in detecting Y chromosome‐linked CNVs, including deletions and duplications, which might broaden our understanding of NOA.